Factors Related To The Compliance Of Pregnant Mothers In Consuming Fe Tablets At Bpm Vera Year 2021 - Diah Pitaloka Tarigan; Basaria Manurung (Institute of Computer Science (IOCS), 2022)
Family support is the closest and inseparable part of the sufferer because with this support it will raise his confidence to face or manage the problems he faces better, as well as people who must obey the suggestions given by the family to support the management of the problem. faced. This study aims to determine the factors related to the compliance of pregnant women in consuming Fe tablets at BPM Vera in 2021. This type of research is an analytical survey research with a cross sectional method approach. The population is all pregnant women at BPM Vera, totaling 36 pregnant women. The number of samples used were 36 people obtained by using total sampling technique. Data analysis technique using chi square. The results obtained in this study were from 36 pregnant women who received family support in compliance with consuming Fe tablets as many as 7 people (19.4%) and 29 people did not receive family support (80.6%), there is a relationship between family support and compliance of pregnant women in consuming Fe tablets with p value = 0.012 <0.05. there is a relationship between age and adherence to consuming Fe tablets, there is a relationship between education and adherence to consuming Fe tablets, there is a relationship between work and adherence to consuming Fe tablets, there is a relationship between family support and adherence to consuming Fe tablets. It is recommended for health workers to increase family support for pregnant women in consuming Fe tablets.